A finite volume scheme on unstructured grids for stiff chemically reacting flows - Riedel, Uwe (Combustion science and technology, 2007)
Obtaining efficient and robust solutions to real reacting flow problems is a challenging task in numerical simulation due to severe nonlinearities in the conservation equations and the wide range of time scales of chemical reactions. However, there are many important industrial applications for such simulations, e.g., premixed and non-premixed combustion, catalytic combustion, or materials processing. A finite volume method on unstructured, non-staggered grids is presented for the solution of two-dimensional low Mach number reacting flows. The conservation law form of the flow equations are discretized in terms of primitive variables. An artificial compressibility method is employed so that low Mach number flows can be solved economically. The equations are marched in time using an implicit extrapolation method. Numerical results are obtained for three different applications: A reaction-diffusion controlled flow in the process chamber of a chemical downstream etch system, the simulation of a premixed ozone flame, and a methane diffusion flame.